2019
DOI: 10.1111/hel.12583
|View full text |Cite
|
Sign up to set email alerts
|

Changes of tight junction and interleukin‐8 expression using a human gastroid monolayer model of Helicobacter pylori infection

Abstract: Background Lack of a model that mirrors Helicobacter pylori‐induced gastric mucosal inflammation has hampered investigation of early host‐bacterial interactions. We used an ex vivo model of human stomach, gastric epithelial organoid monolayers (gastroid monolayers) to investigate interactions of H pylori infection and the apical junctional complex and interleukin‐8 (IL‐8) expression. Method Morphology of human antral mucosal gastroid monolayers was evaluated using histology, immunohistochemical (IHC) staining,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 56 publications
(161 reference statements)
2
14
0
Order By: Relevance
“…8). In consistent with our results, Uotani et al recently demonstrated that H. pylori-infected polarized epithelial cells of human gastroid monolayers largely maintained their normal tight and adherens junctions and TEER, although TEER transiently declined 17 . Furthermore, mucous granule accumulation only occurred beneath the apical plasma membrane and basolateral mis-sorting was not observed in the CagA-expressing cells (Figs.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…8). In consistent with our results, Uotani et al recently demonstrated that H. pylori-infected polarized epithelial cells of human gastroid monolayers largely maintained their normal tight and adherens junctions and TEER, although TEER transiently declined 17 . Furthermore, mucous granule accumulation only occurred beneath the apical plasma membrane and basolateral mis-sorting was not observed in the CagA-expressing cells (Figs.…”
Section: Discussionsupporting
confidence: 94%
“…For example, interleukin-8 (IL-8), a chemoattractant for neutrophils, is thought to play a major role in the H. pylori-associated in ammatory reaction and the level of IL-8 expression has been reported to depend on CagA in gastric cancer cell lines [14][15][16] . However, a recent report using a human gastric epithelial organoid monolayer (gastroid monolayer) model of H. pylori infection demonstrated that IL-8 production showed no signi cant change by infection with either CagA-positive or CagAnegative H. pylori 17 .…”
Section: Introductionmentioning
confidence: 98%
“…46 A recent ex vivo study using human gastroid monolayers demonstrated declined transepithelial electrical resistance following H. pylori inoculation and minimal disruption of ZO-1 or E-cadherin structure were observed by confocal scanning microscopy. 47 Similar to our previous study, 10 female patients with FD were more anxious and had a more impaired QoL than male patients with FD. Emerging evidence provided by recent epidemiological studies indicates that anxiety or depression and functional GI symptoms were positively associated.…”
Section: Discussionsupporting
confidence: 83%
“…When cag PAI‐negative clinical isolates were applied to the gastroid monolayers, they also induced high‐level IL‐8 secretion; no response was observed by cell lines. The authors suggested that this culture model models the human gastric mucosa more closely than cell lines 1 …”
Section: Inflammationmentioning
confidence: 99%